Exploratory Study on the Decision of Integration the Ministries of Education and Higher Education and its Effectiveness on the Educational Sector Output (Survey Study to Explore the Views of Staff at King Abdulaziz University and the Ministry of Educatio - Al-Qurashi, Suzan; Karkshan, Faten (The Arab Journal of Administration, 2018)
The study aimed to identify the expected impact of the decision of the integration the Ministries of Education and Ministry of Higher Education and its effectiveness on the outputs of the education sector through a survey to solicit the views of employees, the researcher relied on field study where the questionnaire was designed according to Likert scale (five point scale) consisting of (25) items consist of four axes; reasons for the merger of the Ministry of Education and Ministry of Higher Education, the goals of the merger, the expected impact of the merger on the curriculum and the expected impact on the growth and development of their employees, and the stability and credibility was measure by Cronbach’s alpha coefficient measure of all axes of the study, which amounted to (0.93), which shows its high stability and reliable in the distribution of the questionnaire. The questioner was distributed electronically, and through which a sample of members of the study population was questioned, the sample included male and female employees in the two Ministries (managers, heads of departments, supervisors, administrators, teachers, teaching staff members), and it is amounted to 130 individuals. In doing statistical analysis and knowing of stability and credibility coefficient, Alpha Cronbach scale, simple linear regression, averages, standard deviations, and weight percentile a number of results was reached including: the existence of a positive effect of the merger of the Ministry of Education and Ministry of Higher Education on the development of public education outcomes, and the arithmetic average is equal to ( 4.38), meaning that the merger of the two Ministries contributes to the development of public education output by 78.5% and will work on the development of employees by 85.25% and that the aim of the integration of the two ministries resolution was of 77.50% from the standpoint of respondents.